PRODUCTION RESPONSE OF CUCUMBER (CUCUMIS SATIVUS L.) PLANTS DUE TO APPLICATION OF Sp-36 AND MANURE - Kaho, Uly J Riwu; Raga, Henny A.; Sole, Robert A.; Naisanu, Joritha; Kisse, Darmanto F; Ndun, Astrid Aryani (International Journal Science and Technology, 2024)
The cucumber plant (Cucumis sativus L.) is a vegetable plant that can be consumed in fresh or processed form. Cucumber production data from 2019-2022 continues to decline. One of the factors causing the decline in cucumber production is cultivation techniques that have not been carried out properly. To increase cucumber production, it is necessary to pay attention to the availability of nutrients. The fertilizer used is SP 36 fertilizer and organic fertilizer. The aim of the research is: To determine the interaction of SP36 fertilizer and manure on the growth and production of the best cucumber plants. The research was carried out in July - August 2023. The design used was a factorial Randomized Block Design (RAK). First factor: SP-36 fertilizer dose consisting of; P1: Control, P2: 150 kg ha-1 equivalent to 60 gpetak-1, P3: 250 kg ha-1 equivalent to 100 gpetak-1, Factor II: manure consisting of: N1: Control, N2: Cow manure 10 tonha-1 is equivalent to 4 kgpetak-1, N3: 10 tonha-1 chicken manure is equivalent to 4 kgpetak-1, Based on the results obtained: The interaction of SP-36 fertilizer and manure has a very real influence on the number of leaves, fruit length, plant height, fruit diameter and fruit weight Keywords: Production, Cucumis sativus L, SP-36, Cow manure